Crystal violet dye sorption over acrylamide/graphene oxide bonded sodium alginate nanocomposite hydrogel. (May 2021) - Pashaei-Fakhri, Sevda; Peighambardoust, Seyed Jamaleddin; Foroutan, Rauf; Arsalani, Nasser; Ramavandi, Bahman
Abstract: The synthesis of acrylamide bonded sodium alginate (AM-SA) hydrogel and acrylamide/graphene oxide bonded sodium alginate (AM-GO-SA) nanocomposite hydrogel was successfully performed using the free radical method. The AM-SA and AM-GO-SA hydrogels were applied as composited adsorbents in crystal violet (CV) dye removal. The adsorption process experiments were performed discontinuously and the acquired data showed that the efficiency is more dependent on pH than other factors. The C–O, CO, and CC groups were detected in the produced hydrogels. The amount of surface area was computed to be 44.689 m 2 /g, 0.0392 m 2 /g, and 6.983 m 2 /g for GO, AM-SA, and AM-GO-SA nanocomposite hydrogel, respectively. The results showed that the experimental data follow the Redlich-Peterson isotherm model. Also, the maximum adsorption capacity of monolayer for CV dye adsorption was determined using AM-SA hydrogel and AM-GO-SA nanocomposite hydrogel 62.07 mg/g and 100.30 mg/g, respectively. In addition, the parameters RL, n, and E showed that the processes of adsorption of CV dye using both types of adsorbents are physical and desirable. Thermodynamically, the CV elimination was exothermic and spontaneous. Besides, thermodynamic results showed that the adsorption process is better proceeding at low temperatures. The experimental data followed a pseudo- second- order (PSO) kinetic model. Also, the Elovich model showed that AM-GO-SA nanocomposite hydrogel has more ability to absorb CV dye. Therefore, according to the obtained results, it can be stated that the produced hydrogels are efficient and viable composited adsorbent in removing CV dye from aqueous solution. Graphical abstract: Image 1 Highlights: Nanocomposite hydrogel (NH) was produced from acrylamide, alginate, graphene oxide. NH had a porous structure with a surface area of 6.983 m 2 /g. A liquid containing crystal violet dye and a real wastewater were treated by NH. The adsorption capacity of crystal violet using NH was obtained ∼100 mg/g. The dye desorption was ∼98% and the number of use cycles was 10 times.